Kinetika redesigning the PE uniform of UP Diliman - Casta, Carl Aaron D.
The university curriculum requires the students to take four (4) PE classes within their stay in UP. It will help them learn to play sports, gain knowledge with other physical activities, and it will also help them to maintain their physical and mental health because it can help the destress from the academic load. Since the students are required to take PE classes, they are also required to wear PE uniforms as most of the professors and coaches do so.